Huaier extract restrains the proliferative potential of endocrine-resistant breast cancer cells through increased ATM by suppressing miR-203 - Sumei Gao (Nature Portfolio, 2017)
Abstract Endocrine therapy is one of the main treatments for breast cancer patients in the early stages. Tamoxifen and fulvestrant are the major drugs of endocrine therapy for breast cancer patients. However, acquired drug resistance often caused treatment failure and relapse for patients, which is a major clinical problem. We investigated whether Huaier extract had effects on endocrine-resistant breast cancer cells. In our study, we aimed to demonstrate the inhibitory effects of Huaier extract on tamoxifen-resistant cells (M7-TR) and fulvestrant-resistant cells (M7-FR). Using MTT and clone formation assays, we found that Huaier extract could inhibit the proliferation in M7-TR and M7-FR cells. Flow cytometry and western blotting illustrated that Huaier extract could induce G0/G1 arrest in both endocrine-resistant breast cancer cells. Mechanistically, we present that Huaier extract significantly increased ataxia telangiectasia mutation (ATM) via down-regulation of miR-203. Huaier extract also had the inhibitory effects on tumour growth in vivo in a xenograft mouse model. These results demonstrated that Huaier extract could inhibit the proliferation of M7-TR and M7-FR cells by increasing ATM via suppression of miR-203.